Hydrocarbon‐related microbial processes in the deep sediments of the Eastern Mediterranean Levantine Basin. Issue 3 (20th December 2013) - Rubin‐Blum, Maxim; Antler, Gilad; Turchyn, Alexandra V.; Tsadok, Rami; Goodman‐Tchernov, Beverly N.; Shemesh, Eli; Austin, James A.; Coleman, Dwight F.; Makovsky, Yizhaq; Sivan, Orit; Tchernov, Dan
Abstract During the 2011 exploration season of the EV Nautilus in the Mediterranean Sea, we conducted a multidisciplinary study, aimed at exploring the microbial populations below the sediment–water interface (SWI) in the hydrocarbon‐rich environments of the Levantine basin. Two c. 1000‐m‐deep locations were sampled: sediments fueled by methane seepage at the toe of the Palmachim disturbance and a patch of euxinic sediment with high sulfide and methane content offshore Acre, enriched by hydrocarbon from an unknown source. We describe the composition of the microbial population in the top 5 cm of the sediment with 1 cm resolution, accompanied by measurements of methane and sulfate concentrations, and the isotopic composition of this methane and sulfate (δ13CCH4, δ18OSO4, and δ34SSO4). Our geochemical and microbiological results indicate the presence of the anaerobic methane oxidation (AOM) coupled to bacterial sulfate reduction (BSR). We show that complex methane and sulfur metabolizing microbial populations are present in both locations, although their community structure and metabolic preferences differ due to potential variation in the hydrocarbon source.